Adaptive incentive-based demand response with distributed non-compliance assessment. (15th November 2022) - Raman, Gururaghav; Zhao, Bo; Peng, Jimmy Chih-Hsien; Weidlich, Matthias
Abstract: Traditional residential incentive-based demand response (DR) programs use fixed incentive structures that do not incorporate closed-loop feedback to compensate for non-compliance by participants. In practice, such programs may not reliably meet their event goals. To address this challenge, real-time feedback can be used to adaptively modify the participants' incentives, an approach which has not been proposed before. This paper proposes a flexible monitoring framework to detect potential non-compliance, whereby a second DR event is adaptively scheduled with higher incentives. In this context, constraints are presented to prevent over-compensation and gaming of the DR system by the participants. This novel dual-event design is implemented using a distributed event-stream monitoring framework to preserve scalability and ensure low monitoring costs. The merits of the proposed DR design are demonstrated at a utility-scale for 100, 000 residents, while also considering the adoption of residential electric vehicles that are poised to increase the flexibility of the demand in the distribution system. Highlights: Residential Demand Response with feedback and adaptive incentives is proposed. A novel multi-event design through distributed event-stream monitoring is detailed. The proposed design ensures scalability and low-cost implementation. Utility-scale results for 100 000 consumers are presented to demonstrate its merits.